ANALYSIS OF SMART CONTRACT IN DECENTRALIZED FINANCE (DEFI) FROM THE PERSPECTIVE OF FIQH MUAMALAH AND MAQĀṢID AL-SHARĪ‘AH - Fanidio Muhammad Ariq Sugiarto; Nur Chanifah; Siti Rohmah (RADJA PUBLIKA, 2026)
The rapid development of blockchain technology has introduced smart contracts as automated digital agreements widely used in the Decentralized Finance (DeFi) ecosystem. These contracts operate without intermediaries and execute transactions based on algorithmic conditions, creating new legal and sharia implications. This study aims to analyze the validity of smart contracts as akad (contracts) within the framework of fiqh muamalah and to formulate regulatory needs based on maqāṣid al-sharī‘ah and positive law. This research uses normative juridical methods with statutory, conceptual, and sharia approaches by examining legal doctrines, regulations, and Islamic jurisprudence principles. The results show that smart contracts can qualify as valid akad if pillars and conditions of contract are fulfilled, including parties, consent, object, and lawful purpose, although digital consent and automated execution require interpretative expansion. From the maqāṣid perspective, smart contracts potentially support protection of wealth (ḥifẓ al-māl), transparency, and efficiency, but also pose gharar and risk if coding errors and regulatory gaps exist. Therefore, integrative regulation and sharia compliance standards are necessary to ensure legal certainty and maslahah in DeFi transactions.